KOMPOSISI BEBERAPA MAKANAN JAJANAN DI JAKARTA - Ignatius Tarwotjo; A. Djaeni Sediautama (Persagi, 1971)
Komposisi beberapa makanan djadjan di Djakarta. (The nutrient composition of some s-nacks in Djakarta) A number of snacks widely consumed in Djakarta were analyzed for their composition of nutrients. They were: